Salivary response of Geoffroy’s spider monkeys (Ateles geoffroyi) to consumption of plant secondary metabolites - Carlos Eduardo Ramírez-Torres; Fabiola Carolina Espinosa Gómez; Jorge E. Morales-Mávil; María Remedios Mendoza-López; Matthias Laska; Laura Teresa Hernández-Salazar (PeerJ)
Geoffroy’s spider monkeys (Ateles geoffroyi) can modulate the acidity-alkalinity (pH) and salivary expression of total proteins (TP) and proline-rich proteins (PRPs) depending on the concentration of tannins in their diet, helping to counteract negative post-ingestive effects. Besides tannins, plants produce a wide variety of secondary metabolites like flavonoids and alkaloids that elicit a bitter taste. Geoffroy’s spider monkeys feed on various plant species and consume different concentrations of secondary metabolites. However, it is unclear whether there is salivary modulation of pH, TP, and PRPs to secondary metabolites other than tannins, or whether this effect also occurs towards bitter substances not associated with secondary metabolites. Therefore, we assessed if there are changes in salivary pH, TP, and PRPs expression towards bitter substances or if spider monkeys display a specific response to secondary metabolites present in their diet and substances not associated with secondary metabolites. We determined the concentration of tannic acid, caffeine and rutin in fruits and leaves in different maturity stages reported as a part of the diet of Geoffroy’s spider monkeys. We presented six adults Geoffroy’s spider monkeys with different concentrations of tannic acid, caffeine, and rutin (0.1, 0.3, 0.6 and one mM) and denatonium benzoate (0.001, 0.003, 0.006 and 0.01 mM) dissolved in a 30 mM sucrose solution. We administered each concentration and collected saliva using swabs (SalivaBio). We used test paper strips to measure the pH and determined the TP concentration using the Bradford method at 595 nm. We also determined the percentage of PRPs using sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE). The results showed marked differences in tannic acid, caffeine and rutin concentration depending on the plant part and species. We found an increase in salivary pH in response to consumption of secondary metabolites, no variations in TP concentration, variations in the percentage of PRPs associated with tannic acid concentrations, and no significant changes when the animals consumed denatonium benzoate. Our results showed that spider monkeys specifically modulate acidity-alkalinity towards secondary metabolites and salivary PRPs expression towards tannic acid in their diet, and that they do not have a generalized salivary response to bitter compounds that are typically considered as toxic substances.